Waste Management Education With Students And KangBurMa - Widiya Avianti; Yayat Rukayat; Arini Permatasari; Farah Fauziyah; Andhika Wiriadinata; Moch Rifki Rahmawan (Inaba of Community Services Journal, 2025)
Waste management is a problem in the city of Bandung, with the landfill Sarimukti accommodating waste that exceeds the capacity of the site. A solution is needed to overcome the accumulation of waste, with the KangBurMa program with students providing education to the community to be able to sort organic and non-organic waste, establish maggot houses, carry out the concept of Buruan Sae as a habit of caring for cleanliness and greening in the KangPisman concept. This Community Service Program activity is beneficial for students, indirectly having practical knowledge and being able to understand the importance of maintaining cleanliness with good waste management and becoming a facilitator in the community, to create a waste-free environment.